Effect of season and proximate composition on the Br, As, Cd and Pb contents in different kinds of key foods consumed in Portugal. (30th December 2019) - Ventura, Marta; Cardoso, Carlos; Bandarra, Narcisa Maria; Delgado, Inês; Coelho, Inês; Gueifão, Sandra; Martins, Marta; Costa, Maria Helena; Castanheira, Isabel
Summary: On the basis of a Total Diet Study, the Br, As, Cd and Pb contents in relevant food groups consumed in Portugal were determined. The studied groups were meat products, fatty fish, lean fish, shellfish, cephalopods, fresh and dried fruit, crucifers and other vegetables. It was observed that the concentrations of As, Br, Cd and Pb in fruit, vegetables and meat products were much lower than in seafood. Fresh fruit exhibited the lowest elemental contents. The concentrations of As, Br, Cd and Pb did not show any dependence on season. With respect to proximate composition, elemental content dependence on protein or ash was weak. PCA showed relevant associations: between Br and ash contents in fatty fish; between Cd, Pb and protein contents in crucifers; and between As, fat and protein contents in the other vegetables group. Therefore, the effect of the proximate composition on the studied elemental contents warrants investigation. Abstract : Overall experimental design of the study.